The Practice of Power by Regional Managers in the Implementation of an Indigenous Peoples Health Policy in the Philippines - Ryan C. Guinaran; Erlinda B. Alupias; Lucy Gilson (Kerman University of Medical Sciences, 2021)
BackgroundIndigenous peoples are among the most marginalized groups in society. In the Philippines, a new policy aimed at ensuring equity and culture-sensitivity of health services for this population was introduced. The study aimed to determine how subnational health managers exercised power and with what consequences for how implementation unfolded. Power is manifested in the perception, decision and action of health system actors. The study also delved into the sources of power that health managers drew on and their reasons for exercising power. MethodsThe study was a qualitative case study employing in-depth semi-structured interviews with 26 health managers from the case region and analysis of 15 relevant documents. Data from both sources were thematically analyzed following the framework method. In the analysis and interpretation of data on power, VeneKlasen and Miller's categorization of the sources and expressions of power and Gilson, Schneider and Orgill's categorization of the sources and reasons for exercising power were utilized. ResultsKey managers in the case region perceived the implementation of the new Indigenous health policy as limited and weakly integrated into health operations. The forms of power exercised by actors in key administrative interfaces were greatly influenced by organizational context and perceived weak leadership and their practices of power hindered policy implementation. However, some positive experiences showed that personal commitment and motivation rooted in one's indigeneity enabled program managers to mobilize their discretionary power to support policy implementation. ConclusionThe way power is exercised by policy actors at key interfaces influences the implementation and uptake of the Indigenous policy by the health system. Middle managers are strategic actors in translating central directions to operational action down to frontlines. Indigenous program managers are most likely to support an Indigenous health policy but personal and organizational factors can also override this inclination.